An unusual case of difficult appendicectomy - Baruah, Arijit Rumu; Baruah, Shyamanta Madhab; Bhuyan, Rupak (International Surgery Journal, 2023)
Vermiform appendix is a tubular lymphoid organ situated about 2 cm below the ileocecal junction on the caecum. The different anatomical positions of the appendix is due to differential growth of the caecum at the time of development. Appendix is now considered to be an important part of the immune system with a distinct function within the gut associated lymphoid tissue and also has a role in bowel repair. Acute appendicitis is probably the most common surgical emergency in the world. Post-ileal appendicitis does not have usual symptoms and signs of appendicitis which makes it difficult for diagnosis and increases the rate of complications. We presented such a case of post-ileal appendicitis which led to a difficult appendicectomy.